Pengaruh Psychological Capital, Relational Attachment, High Performance Work System, Dan High Performfance Work Practice Terhadap Employee Innovative Behavior (GEMA EKONOMI, 2023)
This study aims to analyze the effect of Psychological Capital, Relational Attachment, High Performance Work System, and High Performance Work Practice on Employee Innovative Behavior in the Wealth Management employee division at BUMN bank Jakarta by filling out a questionnaire in the form of a google form using non-probability sampling and the method purposive sampling. This study has a total sample of 195 respondents by distributing questionnaires to employees of the wealth management division. This research uses multiple regression data analysis method. The results of testing the hypothesis in this study indicate that there is a positive influence of Psychological Capital, Relational Attachment, High Performance Work Systems, and High Performance Work Practices on Employee Innovative Behavior in employees of the Wealth Management division at BUMN bank Jakarta. The implications for managerial are expected to be a source of information that can be applied by the wealth management division at the Jakarta BUMN bank to improve the performance and work quality of the employees of the wealth management division at the Jakarta BUMN bank. Good Psychological Capital is needed where positive psychological conditions and optimism exist in the workforce. can encourage innovative behavior in the corporate environment. Second, to improve the company's work results, a relational attachment is urgently needed so that a relational attachment can be one of the driving factors for the emergence of positive innovations in the behavior of employees in the wealth management division at Bank BNI Pejompongan. Third, improving the High Performance Work Practice and High Performance Work System in the wealth management division at Bank BNI Pejompongan can be done through regular job evaluations, employee training and development and improvement of employee welfare according to each portion. Thus it can be realized to support good Employee Innovative Behavior.